Islamic headscarves: the other-religion effect and religious literacy at the european court of human rights - ÜNLÜ, NESRİN (My University, 2023)
Islamic headscarves continue to be one of the most controversial issues concerning Muslims across Europe. In order to analyse how the headscarf is evaluated through the prism of human rights values and moral principles in Europe, this article revisits some headscarf cases heard at the European Court of Human Rights (ECtHR). The weaknesses in the rulings have been widely examined but this article will focus on the religious individual, her agency, and the link between her and her associated group, which have been less discussed in the literature. The article highlights that the modern socio-political structure of the Council of Europe countries is strikingly different from that of their premodern counterparts. Thus, the contours of religious groups, the link between an individual and her associated group, and the positioning of various religious groups vis-a-vis the state require a set of approaches to a religious claim centred on the individual believer. This can be clearly observed in the theoretical underpinnings of the European Convention on Human Rights, which, however, are not pursued adequately in practice because the actual rulings not only involve logic but also include perception.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Religious freedom; Article 9 of the European Convention on human rights; Muslim women and agency; secularism; state neutrality; law and religion